DAYA SAING PRODUK KELAPA INDONESIA DAN EKSPORTIR KELAPA UTAMA LAINNYA DI PASAR GLOBAL - Suprehatin; Hanief Al Naufal (Jurnal Penelitian Pertanian Terapan, 2021)
The global value chains increase competitiveness of the trade of agricultural and food products including coconut and its derivatives products such as coconut oil and copra. This study aims to analyze the position and correlation of Indonesia's coconut competitiveness among other top exporter countries in the global market. The Trademap’s panel data from 2012 to 2017 are used and analyzed by Revealed Symmetric Comparative Advantage (RSCA), Trade Specialization Index (ISP), and rank Spearman correlation. The results show that all Indonesian coconut products have competitiveness in the global market and already reach a mature phase. The highest competitiveness of the Indonesia coconut products is coconut in the inner shell. The results also show that Indonesia has a strong competitive correlation with The Philippines, Thailand, and Papua New Guinea for three different coconut products